Digital transformation in the transport and logistics sector of Kazakhstan: Challenges and opportunities for global integration - G. Saktaganova; A. Karipova; D. Mukhiyayeva; G. Zhanseitova; I. Saktaganova (Науковий вісник Мукачівського державного університету. Серія Економіка)
The purpose of the study was to identify the key advantages and challenges of digitalisation in the transport and logistics sector of Kazakhstan and assess its impact on economic growth and international cooperation. The study employed methods of analysis, evaluation, and forecasting to determine the effects of digital technologies on various dimensions of the transport and logistics system of Kazakhstan, including productivity, investment appeal, and global integration. Findings indicated that digital transformation enhances effectiveness, reduces transaction costs, and improves investment attractiveness of the sector. The introduction of digital platforms, automation of customs procedures, and use of artificial intelligence (AI) accelerated cargo processing and optimised operations. Analysis indicated that digitalisation fosters growth in foreign investment by increasing transparency and predictability in transport processes. Private infrastructure investments were projected to reach USD 500-800 million, yielding returns of 15-20% over 3-5 years, while public subsidies may amount to USD 200-300 million with returns of 10-12% over 1-3 years. International projects are estimated to generate USD 600-900 million in investment with expected returns of 18-25% over 4-6 years. Public-private partnerships are anticipated at the level of USD 400-600 million, offering returns of 12-18% over 2-4 years, and investments in start-ups are expected to total USD 100-200 million with returns of 25-35% over 2-3 years. The development of digital solutions across international transport corridors strengthened the role of Kazakhstan as a logistical hub. However, major challenges persisted, including inadequate digital infrastructure, cyber threats, low levels of digital literacy, and financial constraints faced by small and medium-sized enterprises. Effective transformation requires strong public-private cooperation and the creation of “smart” logistics hubs. Digitalisation within the transport and logistics sector thus presents substantial potential for positioning the country as a leading logistical hub in Central Asia